Моделирование напряженно-деформированного состояния болтового соединения рабочего колеса гидротурбины на основе 3D модели - Евдокимов, Н. Н.; Степченко, А. С.; Трубаев, Александр Иванович (НТУ "ХПИ", 2009)
Розроблено методику аналізу напружено-деформованого стану болтових з'єднань робочих коліс гідротурбін на основі моделювання циклічно симетричної частини конструкції. Проведено аналіз параметрів напружено-деформованого стану з урахуванням всіх навантажень, що виникають у процесі монтажу і експлуатації гідротурбіни. Наведені результати розрахунку для різних температурних режимах термозатягування болтів.

In the work it has been developed the technique of the analysis of the stress-strain state of bolted connections of hydraulic turbine driving wheal on the basis of simulation cyclically a symmetric part of a construction. The analysis of the stress-strain state parameters taking into account assembling and exploitation loadings arising in hydraulic turbine is carried out. Results of calculation for different temperature conditions of a thermo-inhaling of bolts are introduced.
Keywords: эксплуатация гидротурбин; Днепровская ГЭС; разрушение болтовых соединений; метод конечных элементов; термозатяжка; пластические деформации